On and off the rails [videorecording (DVD)]. - Anstey, E. H. (Edgar H.), 1907-1987; Nicholls, Nick; Thompson, Tony; Shearman, John director; Craigen, Ronald (British Transport Films collection, 2007)
In 1948, the British Transportation Commission set up its own in-house film production unit led for 25 years by Edgar Anstey -- a founding father of the British documentary movement. it became one of the largest industrial film units in Britain. In this selection of films the documentary aficionado will recognise the development of traits and innovations in British non-fiction filmmaking.